Detection and molecular characterisation of bovine corona and toroviruses from Croatian cattle - Lojkić, Ivana (BMC Vet Res, 2015)
BACKGROUND: Bovine coronavirus (BCoV) together with bovine torovirus (BToV), both members of the Coronaviridae family, order Nidovirales are the most common viral enteric pathogens. Although studied separately, their joint occurrence and the molecular diversity in cattle in Croatia have not been investigated. METHODS: A survey is carried out on 101 fecal samples from diarrheic young and adult cattle during the 3-year period from i) one large dairy herd, ii) four small herds and iii) three nasal and paired fecal samples from calves with symptoms of respiratory disease. Samples were submitted to RT-PCR and sequencing for BCoV Nucleocapsid gene, BCoV Spike gene and BToV Spike gene. RESULTS: BCoV was detected in 78.8 % of fecal samples from symptomatic cattle and three nasal and paired fecal samples from calves with respiratory symptoms. BToV was detected in 43.2 % of fecal samples from symptomatic cattle and a fecal sample from calves with respiratory symptoms. Molecular characterisation of those viruses revealed some nucleotide and aminoacid differences in relation to reference strains. CONCLUSIONS: BToV should be regarded as a relevant pathogen for cattle that plays a synergistic role in mixed enteric infections.